Sustainability Disclosure and Performance of Quoted Oil & Gas Companies in Nigeria - Alexander Olawumi DABOR; Victor ODU; Ene- Mari OCHA (International Journal of Environmental, Sustainability, and Social Science, 2024)
Many environmentalists have argued that corporations are to be held accountable for environmental hazards that they unleash on the environment. This study seeks to ascertain the effect of sustainability disclosure on firm performance. This study focused on the Nigerian oil and gas sector. This sector has been in the turbulent waters in recent times. The spillover effect of climatic change and drastic environmental degradation has fueled the agitation for sustainability disclosure the world over. This study employed a judgmental sample technique to select ten firms for a period of ten years, 2014- 2023. The results showed that disclosure of economic activities has a positive effect on firm performance, while disclosure of social activities has a negative on firm performance. This study was performed to give cradle to prior studies and to reaffirm the results obtained by prior researchers on the subject. The result shows that disclosure of economic activities by firms in the industrial subsector in Nigeria positively influences the financial performance of firms within this biome. The result further reveals that disclosure of environmental activities by firms in the industrial goods sector in Nigeria has no significant effect on financial performance. Finally, the results reveal that disclosure of social activities by firms in the industrial goods subsector has a negative effect on the financial performance of firms in this biome.